Personas - User Focused Design - Nielsen, Lene (Human-Computer Interaction Series,, 2013)
People relate to other people, not to simplified types or segments. This is the concept that underpins this book. Personas, a user centered design methodology covers topics from interaction design within IT, through to issues surrounding product design, communication, and marketing. Project developers need to understand how users approach their products from the product's infancy, and regardless of what the product might be. Developers should be able to describe the user of the product via vivid depictions, as if they - with their different attitudes, desires and habits - were already using the product. In doing so they can more clearly formulate how to turn the product's potential into reality. With contributions from professionals from Australia, Brazil, Finland, Japan, Russia, and the UK presenting real-world examples of persona method, this book will provide readers with valuable insights into this exciting research area. The inspiration to create user descriptions includes character-driven narratives, and the film Thelma & Louise is analyzed in order to understand how the development process can also be an engaging story in various professional contexts. With a solid foundation in her own research at the IT University of Copenhagen and more than five years of experience in solving problems for businesses, Lene Nielsen is Denmark's leading expert in the persona method. She has a PhD in personas and scenarios, and through her research and practical experiences she has developed her own approach to the method - 10 Steps to Personas. Personas - User Focused Design presents a step-by-step methodology of personas which will be of interest to developers of IT, communications solutions and innovative products.